2015
DOI: 10.4238/2015.august.7.21
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene FokI, TaqI, BsmI, and ApaI polymorphisms and susceptibility to pulmonary tuberculosis: a meta-analysis

Abstract: ABSTRACT. The aim of this study was to determine whether vitamin D receptor (VDR) genetic polymorphisms are associated with the susceptibility to pulmonary tuberculosis (PTB). MEDLINE and Embase databases and manual literature searches were used. A meta-analysis was conducted on the associations between the VDR FokI, TaqI, BsmI, and ApaI polymorphisms and PTB susceptibility. A total of 16 studies comprising 3231 patients and 3670 controls met the study inclusion criteria, consisting of 14 studies on the VDR Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…Vitamin D is involved in cell-mediated immunity where it is thought to reduce the production of inflammatory cytokines such as IL-1, IL-6, and TNF-α that are involved in the spontaneous preterm birth [14,15]. Polymorphisms in the VDR gene have been associated with autoimmune and infectious diseases such as tuberculosis, Crohn's disease, asthma or diabetes [16][17][18][19]. Maintenance of a normal pregnancy requires efficient coordination of antimicrobial and anti-inflammatory responses within the feto-placental unit.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is involved in cell-mediated immunity where it is thought to reduce the production of inflammatory cytokines such as IL-1, IL-6, and TNF-α that are involved in the spontaneous preterm birth [14,15]. Polymorphisms in the VDR gene have been associated with autoimmune and infectious diseases such as tuberculosis, Crohn's disease, asthma or diabetes [16][17][18][19]. Maintenance of a normal pregnancy requires efficient coordination of antimicrobial and anti-inflammatory responses within the feto-placental unit.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular-based epidemiological studies have identified several functional polymorphisms in the VDR [21] and have demonstrated that the variants can affect the function of the receptor by altering its affinity to vitamin D [28,29]. VDR genetic variants have previously been associated with a number of diseases including pulmonary tuberculosis, diabetes, osteoporosis, asthma, ulcerative colitis, breast and female reproductive cancers, melanoma, systemic lupus erythematous and rheumatoid arthritis, Parkinson's disease, and coronary artery disease [30][31][32][33][34][35][36][37][38][39]. Pharmacogenetic studies have shown that VDR polymorphisms can modulate the response to a number of drugs including anti-tubercular and anti-psoriatic medications, anti-osteoporotic agents in postmenopausal women, interferon and ribavirin in patients with hepatitis C, vitamin D supplementation, and calcitriol [40][41][42][43][44][45][46], as well as with statin-induced myopathy [47].…”
Section: Discussionmentioning
confidence: 99%
“…Also, all the included studies were of good to modest quality fulfilling the preset needful criteria as tested by NOS quality assessment scale. Although, plenty of meta–analyses have been performed in the past considering various case–control studies analyzing this relationship selected from various databases and concluded accordingly [4749]. For example, a recent pooled study by Lee and Song [49], based on eight studies reported that Bsm I polymorphism is not associated with risk of PTB.…”
Section: Discussionmentioning
confidence: 99%